Alienação parental : uma discussão a partir dos direitos fundamentais da criança e do adolescente - Amato, Gabriela Cruz (2014)
This study aims to analyze the fundamental rights of children and adolescents across the acts of parental alienation, with the aim of identifying which rights of children and adolescents may be violated by the Institute of parental alienation, seeking to achieve possible legal solutions for this highly psychological problem. Starting from an examination of the evolution of children's rights, and constitutional openness to the recognition of these rights, we will analyze the structure of fundamental rights through his general theory, to finally get to the study of fundamental rights in kind, capable of being impaired the practice of parental alienation. Also for this purpose, will be elucidated the principles of protection of children and adolescents, disposed in Federal Constitution of 1988, the Statute of Children and Adolescents, and also in international documents such as the Convention on the Rights of the Child 1989. Performed such considerations, finally, we need to check those relating to parental alienation issues. Therefore, the distinction between the Parental Alienation Syndrome and parental alienation will be held, concluding that interests the right to legal protection of parental alienation in order to avoid psychological effects, and even curbing this practice. It is pointed out shared custody as a possible helper tool in resolving these conflicts.